TERRITORIAL INTEGRITY AND SELF-DETERMINATION UNDER THE UNITED NATIONS CHARTER: THE RENEWED BIAFRA SECESSIONIST CLAIM IN NIGERIA - Innocent Aja, Ngene; Emmanuel Chinagorom, Alita; Chinonso Ogba, Michael (African Journal of Social and Behavioural Sciences, 2026)
The tension between territorial integrity and the right to self-determination remains one of the most contested issues in international law, particularly in post-colonial states confronting renewed separatist movements. Yet, while international legal scholarship largely emphasizes the primacy of territorial integrity under the United Nations Charter, less attention has been paid to how domestic political grievances sustain secessionist mobilization even when legal claims lack international validity. This study examines this dilemma through the resurgence of the Biafra secessionist claim in Nigeria. Drawing on Relative Deprivation Theory, the study explains how perceived political, economic, and representational marginalization can generate collective grievances that sustain separatist agitation. Using qualitative documentary analysis, the research interrogates whether the Indigenous People of Biafra’s (IPOB) demands align with international norms of self-determination, the socio-political drivers of the renewed secessionist agenda, and the implications for national stability. The findings indicate that, although international law strongly protects Nigeria’s territorial integrity and does not legitimize unilateral secession, persistent perceptions of marginalization among sections of the Igbo population contribute to a continuing internal self-determination deficit. The study, therefore, argues that legal prohibition alone cannot extinguish secessionist claims when governance grievances remain unresolved, highlighting the need for inclusive governance, constitutional dialogue, and rights-based federal reforms.